Targeted killing in international law - Melzer, Nils. (Oxford ; New York : Oxford University Press, 2008)
This title examines the international lawfulness of state-sponsored targeted killings in military and police operations. Analysing recent state practice and jurisprudence, it establishes when targeted killing may be considered lawful, and what legal restraints are imposed on the practice in times of war and peace.
The notion of 'targeted killing' -- Current trend towards legitimization -- Targeted killing in contemporary legal doctrine -- The analysis -- The paradigm of law enforcement -- Law enforcement and the conventional human right to life -- Law enforcement and the protection of life under international humanitarian law -- Law enforcement and the non-conventional human right to life -- Permissibility of targeted killing as a method of law enforcement -- The paradigm of hostilities -- The principle of distinction under international humanitarian law -- Means and methods in the conduct of hostilities -- Human rights law and the paradigm of hostilities -- Permissibility of targeted killing as a method of conducting hostilities -- Comparative conclusions -- Epilogue : targeted killing and the rule of law.
Includes bibliographical references (pages 445-458) and index.
Keywords: Targeted killing; Human rights; Law enforcement; Human Rights; Targeted killing; Law enforcement